Triggers and mediators of epigenetic remodeling in plants - Comai, Luca (Frontiers in Epigenetics and Epigenomics, 2023)
Plant epigenetic studies have revealed that developmental or environmental events can trigger both local and global epigenetic remodeling. These changes result in mitotically and even meiotically persistent states that impact phenotype and could contribute to its plasticity. The challenge is to understand the mechanisms that trigger remodeling, their action, their evolutionary role, and their potential in breeding.